Fast Steady-State And Transient Analyses Of Mems Devices - Loh , Jit Seng (2010)
Finite element simulation plays a crucial role in development of MEMS (MicroElectroMechanical Systems) devices by providing accurate upfront characterization of its multi-physics behaviour, but it also requires substantial amount of computational time. To address this deficit, the concept of using beam model is specifically introduced in this thesis to achieve efficient and accurate steady-state finite element simulation of electro-thermal micro-actuators. Beam model can achieves high computational efficiency by reducing the total degrees of freedoms involved to only those necessary for sufficiently accurate estimate of the bulk mechanical behaviour, while accounting for material non-linearity to ensure solution accuracy. Good correlation is obtained when compared to using three-dimensional finite element model, where the deviation is less than 4% but with more than one order of computational time reduction in all five case studies. Based on this beam model, parametric studies are also efficiently conducted to investigate the effects of geometrical dimensions on the output efficiency of various electro-thermal micro-actuators. In addition, Asymptotic Waveform Evaluation (AWE) method is also introduced in this thesis to efficiently and accurately solve linear dynamics finite element simulation of any MEMS devices in general. Based on the concept of approximating the original three-dimensional finite element model with a reduced order model, AWE method can provide equivalent accuracy as conventional numerical time integration method, but at significantly less amount of computational time. In this thesis, AWE method has been successfully applied to build reduced-order models for a micro-actuator, micro-hotplate and also micro-accelerometer, and it is shown that the achieved computational time reduction is at least one order with less than 4% deviation when compared to ANSYS® solution. Besides that, it is demonstrated that AWE is capable of handling various complex boundary conditions, enabling it to solve various practical engineering problems.